Al-Qalb as the Core Element of Thought and Action: A Literature Review - Roslan, Muhammad Zickryl Hakim; Ismail, Nor Hanani; Rofie, Mohamad Khadafi (Academic Inspired Network (AIN), 2023)
In Islam, al-Qalb (heart) is described as a tool of thinking and storing of knowledge. Terms such as tafaqquh, ta’aqul are connected to the word al-Qalb. In addition, al-Qalb is also associated with a person’s intention or determination before taking actions and making decisions. Those who are given wisdom or intelligence also use al-Qalb to think. These descriptions give rise to one question. What do the scholars discuss on the concept of al-Qalb as the core element of thought and action? The paper aims to analyse the highlights of al-Qalbrelated works using content analysis. This study showcases the concept of al-Qalb as the core element of thought and action